COMMUNITY ENGAGEMENT PLAN ONLINE STUDENTS HELP FOR INDONESIAN SCHOOL IN RIYADH, SAUDI ARABIA - Dwi Nisa Widhawati (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
Indonesian School in Riyadh (ISR) was established in 1985 by Indonesian embassy in Riyadh in purpose to accommodate the students from Kindergarten to Year 12. The school educates students in three languages: Indonesian, Arabic and English (Setyono, 2016). The ISR has no selection system on students’ competencies for enrolment process like in the home country. The school is only one option for Indonesian children in Riyadh where students from various backgrounds are accepted. Online students’ help is design eLearning in purpose to improve students’ achievement. The school has 399 students and 21 employees, including four non-teachers and one librarian. The ISR has characteristics like public school in Indonesia where curriculum, policy and finance are supported by Indonesian government and parents’ committee partnership (Setyono, 2016). Based on the concept of No Children Left Behind (NCLB), the ISR need to give opportunities for students to continue to study at they preferred school or university in Indonesia and Saudi Arabia. In these contexts, the community engagement strategies plan is not only collaboration of stakeholders to accommodate learning facilities, but also provide eLearning tools to support the learners need in purpose to improve students’ competencies and create positives learning environment in ISR.